Uterine sarcomas - Giampietro, Alfonso (2015)
We bring to the attention of the Peruvian colleagues 2 cases of uterine sarcoma, which recently had at the Clinic headed by Professor JJ Crottogini and we are honored to belong. This is a work of the clinic to which we belong. In addition we tried to collect cases of sarcoma that exist in our environment and we do not know if they are all at least are those who are documented, being published for the knowledge of them.